Sucrose, Cobalt Chloride and Aerated Soft Drink Improves the Vase Life and Quality of Cut Scapes of Hemerocallis fulva - Arief, Z Mohmad; Tahir, Inayatullah (Journal of Postharvest Technology, 2015)
A study was conducted to examine the post-harvest characteristics of cut  scapes of Hemerocallis fulva cv. Royal Crown. The scapes were harvested at  0900 hrs., one day before anthesis of the first bud. The scapes were held in  following test solutions: Soft Drink (25%); Soft Drink (25%) + Sucrose (0.15M) and Soft Drink (25%) + Sucrose (0.15M) + CoCl2 (0.2mM). Distilled  water alone served as control. Soft Drink (25%) +Sucrose (0.15M)  significantly prolonged the vase life of scapes by six days as compared to  control. Besides significantly increasing the number of blooms per scape,  larger flower diameter was maintained in this treatment. The total acetone  extractable pigment content of the perianth tissue of scapes held in this  treatment was almost doubled as compared to control. When CoCl2 (0.2mM)  was added to this test solution containing Soft Drink (25%) + Sucrose (0.15M), the effects were much more pronounced and the solution uptake was  significantly promoted. The present results suggest that Soft Drink (Limca) in  combination with Sucrose (0.15M) + CoCl2 (0.2mM) can serve as an effective  vase solution for the enhancement of vase life and postharvest quality of the  cut flowers of Hemerocallis fulva.
Keywords: Cobalt Chloride; Cut flowers; Hemerocallis fulva; Soft drink; Vase Life